2014
DOI: 10.1111/cid.12201
|View full text |Cite
|
Sign up to set email alerts
|

A 1‐Year Prospective Clinical and Radiographic Study of Early‐Loaded Bone Level Implants in the Posterior Maxilla

Abstract: Bone level implants with the SLActive surface placed into low-density bone and loaded after 6 weeks of healing can predictably achieve and maintain a successful tissue integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
2
24
1
1
Order By: Relevance
“…Additionally, this study reported that even in these medically compromised patients, it was possible to achieve stable implant stability after the initial bone remodeling, although implant stability values were significantly lower than in the moment of insertion from the first and third postoperative week in the SLActive and SLA group, respectively. The results of present research do not correlate with the findings of previous studies, where ISQ in the end of follow-up period exceeded the baseline values (Huwiler et al 2007;Han et al 2010;Markovic et al 2015). These somewhat lower ISQ values in present research might be attributed to the coumarin medication and its effect on bone tissue.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, this study reported that even in these medically compromised patients, it was possible to achieve stable implant stability after the initial bone remodeling, although implant stability values were significantly lower than in the moment of insertion from the first and third postoperative week in the SLActive and SLA group, respectively. The results of present research do not correlate with the findings of previous studies, where ISQ in the end of follow-up period exceeded the baseline values (Huwiler et al 2007;Han et al 2010;Markovic et al 2015). These somewhat lower ISQ values in present research might be attributed to the coumarin medication and its effect on bone tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…; Markovic et al. ). These somewhat lower ISQ values in present research might be attributed to the coumarin medication and its effect on bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…; Marković et al. ). The high success rates obtained in this study can be explained by high primary stability at placement.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the improvement in implant surface technologies, with the development of microrough hydrophilic surfaces, has allowed to significantly accelerate the osseointegration process (Calciolari et al, 2017;Donos et al, 2011;Lang et al, 2011), with the possibility to functionally load the implants already 3-6 weeks after implant placement both in the anterior and posterior areas (Bornstein, Wittneben, Bragger, & Buser, 2010;Markovic et al, 2015;Morton et al, 2010).…”
mentioning
confidence: 99%